2020
DOI: 10.1007/s42690-020-00127-6
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide resistance management against thrips (Thysanoptera: Thripidae) on onion in the central Rift Valley of Ethiopia

Abstract: Two field experiments were conducted in the Central Rift Valley of Ethiopia in the hot and cool dry seasons of 2016/2017 with the objective to develop an insecticide resistance management program on thrips infesting onion. The first experiment dealt with the evaluation of four different insecticides namely profenofos, λ-cyhalothrin, imidacloprid, and spinetoram in different sequences on thrips population and their effect on yield. The second experiment examined the effect of admixing the surfactant organosilic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Zakia et al (2016) decided that the adjuvants Argal (trisiloxane ethoxylate) gave the highest increase in average residual effect than the pesticide alone. Dewer et al (2017) concluded that adjuvants PEG 600 di-laurate, Extravon ® , and Codacide oil in combination with the tested insecticides at their half-recommended field rate gave a good potential for untreated checking the Egyptian cotton leafworm, (Negash et al 2020) who stated that Surfactant added insecticides gave fewer numbers of thrips and higher yields than the corresponding insecticides applied without surfactant.…”
Section: Discussionmentioning
confidence: 99%
“…Zakia et al (2016) decided that the adjuvants Argal (trisiloxane ethoxylate) gave the highest increase in average residual effect than the pesticide alone. Dewer et al (2017) concluded that adjuvants PEG 600 di-laurate, Extravon ® , and Codacide oil in combination with the tested insecticides at their half-recommended field rate gave a good potential for untreated checking the Egyptian cotton leafworm, (Negash et al 2020) who stated that Surfactant added insecticides gave fewer numbers of thrips and higher yields than the corresponding insecticides applied without surfactant.…”
Section: Discussionmentioning
confidence: 99%
“…In laboratory and field applications of chlorantraniliprole and flubendiamide, the addition of adjuvants increased the mortality of A. transitella (DEMKOVICH et al, 2018). Adjuvants added to fipronil, lambda-cyhalothnin, and dimethoate sprays also increased the control efficacy of T. tabaci (GANGWAR et al, 2016;NEGASH et al, 2020) and the biological activity of chlorantranilprole against Anticarsia gemmatalis (HüBNER, 1818) (Lepidoptera: Erebidae) (ARRUÉ et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that adjuvants added to diamides increased the mortality of adults of Amyelois transitella (Walker, 1863) (Lepidoptera: Pyralidae) (DEMKOVICH et al, 2018). This was also verified when adjuvants were added to indoxacarb and cartap to control Neoleucinodes elegantalis (Guenée, 1854) (Lepidoptera: Pyralidae) (DE BORTOLI et al, 2013), to thiamethoxam + lambda-cyhalothrin against Enneothrips flavens Moulton, 1941 (Thysanoptera: Thripidae) (CALORE et al 2015), and dimethoate and spinetoram to control Thrips tabaci Lind., 1888 (Thysanoptera: Thripidae) (NEGASH et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Plots treated with wood tobacco and karate 5 achieved tuber yields of > 30% compared to controls. Many studies have reported that higher bulb yields were obtained with insecticides that reduced thrip density (Negash et al, 2020). When onion thrips infestations remained above economic threshold levels, crop damage, and lower yields occurred.…”
Section: Effects Of Insecticides and Varieties Integration On Yield C...mentioning
confidence: 99%